The culture of crime - LaMay, Craig L.; Dennis, Everette E. (Transaction Publishers, 1995)
The wicked world: the National Police Gazette and gilded-age America / Elliott J. Gorn -- Cosmology of fear / Steven Gorelick -- The reporter I: cops, killers and crispy critters / David Simon -- The victim: twice wounded / Ellen Levin -- The criminal: where the sun don't shine / Federal I.D. No. 03144-999 -- The cop: waiting for good dope / Kim Wozencraft -- The lawyer: "A chill wind blows" / William M. Kunstler -- The judge: justice in prime time / Thomas S. Hodson -- The court officer: meet the press / Rebecca Fanning -- The reporter II: better than real life / Edna Buchanan -- Nervous in the naked city / Howard Rosenberg -- Kids and crime / Michele Magar -- The female fear / Margaret T. Gordon -- Firearms follies : how the news media cover gun control / Ted Gest -- Desparadoes and lawmen: the folk hero / Richard Maxwell Brown -- Making a killing: an interview with Elmore Leonard / Craig L. LaMay -- You want me to read a what? /Peter A. Levin -- Raskolnikov's regret: covering crime in Russia / Alexei Izyumov -- Glimpses of Gotham / Robert W. Snyder